The Quantity and Quality of Education and their Influence on Earnings: The Case of Chemical Engineers - Link, Charles R. (The Review of Economics and Statistics, 1973)
IN this paper is examined some of the determinants of earnings of males in a high powered occupation, chemical engineering. Models such as those developed here can be useful to researchers interested in earnings functions, the theory of occupational choice, economic growth and returns to investments in human capital. In addition, earnings models can be help'ful to individuals who must make promotion and salary decisions. The impact of education on earnings has received a great deal of attention in social, political and economic circles. Previous studies show that persons who obtain higher levels of education earn higher incomes. However, comparing average incomes of individuals who differ only in levels of educational attainment may overstate the influence of education since schooling and non-schooling factors other than the amount of formal schooling cause differences in individual incomes. Such factors include socio-economic background, demographic characteristics, innate ability and the quality of formal education. Emphasis in this study is on the quality of education and student ability. The author was able to find only two attempts at simultaneously estimating the impact of student ability and school quality on the earnings of persons in professional occupations.' This paper is viewed as an exploratory effort in this direction. The basic earnings functions to be estimated are described in section I. The data sources, key proxy variables in the regression analysis and the regression findings are discussed in section II. Section III is a summary of the main findings.